Recollections of childhood and imagined nation in the collected letters of Jose María Arguedas - Núñez, Gabriela (2016)
This article explores the memories of childhood that Jose Maria Arguedas reconstructs in his letters and the recreation and imagination of himself as a symbol of the Peruvian nation. His recollections portrait ambivalent feelings of suffering and tenderness, with special attention to the need of protection, as well as the identification with the oral expression and the Andean world view, creating a new sense of otherness: one that is more connected to the emotions. Arguedas stablishes himself as a living bridge in Peruvian culture and as the reincarnation of a diverse country, filled with contradictions.